The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/2040-2384-2-26
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in old-aged subjects after ischemic stroke: a cautionary note for investigators

Abstract: Angiogenesis represents a form of neovascularisation of exceptional importance in numerous pathological conditions including stroke. In this context it is directly related to neuroregeneration which is seen in close proximity. However, numerous experimental data have been drawn from studies that have ignored the age criterion. This is extremely important as angiogenesis is different in young versus old subjects. Extrapolating data obtained from studies performed in young subjects or "in vitro" to old-age patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 97 publications
(104 reference statements)
1
35
0
Order By: Relevance
“…This concurs once again with the findings of two studies that analyzed the Sleep Heart Health Study cohort, which showed an increase in the incidence of new cardiovascular events caused by heart failure in the subgroup of elderly patients with OSA (25) or stroke (median age of stroke patients: 72 years) (27), although cardiovascular mortality was not analyzed in these studies. Although it could be supposed that the 'ischemic preconditioning' hypothesis would endorse protection against intermittent hypoxia in any type of cardiovascular event, most of the data available on this compensatory mechanism derive from studies investigating its effect on coronary circulation (38)(39)(40), and the effect on cerebral circulation is much more open to debate, particularly in the case of elderly people (41)(42)(43). Thus, Wegener et al reported that the protection provided against stroke development by an earlier period of cerebral ischemia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This concurs once again with the findings of two studies that analyzed the Sleep Heart Health Study cohort, which showed an increase in the incidence of new cardiovascular events caused by heart failure in the subgroup of elderly patients with OSA (25) or stroke (median age of stroke patients: 72 years) (27), although cardiovascular mortality was not analyzed in these studies. Although it could be supposed that the 'ischemic preconditioning' hypothesis would endorse protection against intermittent hypoxia in any type of cardiovascular event, most of the data available on this compensatory mechanism derive from studies investigating its effect on coronary circulation (38)(39)(40), and the effect on cerebral circulation is much more open to debate, particularly in the case of elderly people (41)(42)(43). Thus, Wegener et al reported that the protection provided against stroke development by an earlier period of cerebral ischemia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that angiogenesis is not always detected in peri-infarct area. Aging is a complex and significant factor that impacts post-ischemic angiogenesis (Petcu et al, 2010). Hypoxia-inducible angiogenesis in rodent hippocampus decreases with aging (Ingraham et al, 2008).…”
Section: The Role Of Angiogenesis In Cerebrovascular Diseases Andmentioning
confidence: 99%
“…Two key parameters influence restoration of blood flow: presence of collaterals and a capacity to undergo vascular remodeling and produce angiogenic mediators. A majority of the research reveals that spontaneous vascular remodeling occurs after TBI and stroke [71,72 ▪ ,73] with exceptions that show the absence of vascular remodeling depending upon the region of assessment [74], impaired plasticity and remodeling associated with age [7577] and comorbid conditions [78,79]. Vascular modeling is associated with improved neurological outcomes [73].…”
Section: Reparative Neovascularization After Stroke and Traumatic Bramentioning
confidence: 99%